2010
DOI: 10.2320/matertrans.l-m2010802
|View full text |Cite
|
Sign up to set email alerts
|

Texture Randomization of AZ31 Magnesium Alloy Sheets for Improving the Cold Formability by a Combination of Rolling and High-Temperature Annealing

Abstract: To improve the cold formability of AZ31 magnesium alloy sheets, we investigate texture control by rolling and annealing. The texture ideal for forming close to random orientation was obtained by annealing at 773 K before and after isothermal rolling at 298-573 K. For the randomizing process, such a high temperature in pre-annealing was essential, whereas a slightly lower temperature was acceptable for final annealing, assuming a sufficiently long annealing time. The randomized sheet could be obtained in a wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Figure 4 gives f10 10g, {0001} and f10 11g pole figures (stereographic projection) and their ¤ 2 = 0°ODF sections of the magnesium alloy AZ31 before and after warm press deformation. These pole figures show strong h0001i == ND basal textures with the dual-peak characteristics, similar to those from X-ray diffraction, 22,23) which confirms that the cubic samples of light metals such as Mg and Al can be employed to directly measure the bulk textures and the correction to neutron absorption can be ignored. Moreover, the neutron diffraction results show that the strongest pole figures before and after warm press are both f10 10g, not {0001}, and the ODFs exhibit that the preferred orientation with the maximum intensity is f 12 11gh10 10i at (¤ 1 = 0°, º = 72.89°, ¤ 2 = 0°) which becomes stronger after warm press deformation.…”
Section: Resultsmentioning
confidence: 49%
“…Figure 4 gives f10 10g, {0001} and f10 11g pole figures (stereographic projection) and their ¤ 2 = 0°ODF sections of the magnesium alloy AZ31 before and after warm press deformation. These pole figures show strong h0001i == ND basal textures with the dual-peak characteristics, similar to those from X-ray diffraction, 22,23) which confirms that the cubic samples of light metals such as Mg and Al can be employed to directly measure the bulk textures and the correction to neutron absorption can be ignored. Moreover, the neutron diffraction results show that the strongest pole figures before and after warm press are both f10 10g, not {0001}, and the ODFs exhibit that the preferred orientation with the maximum intensity is f 12 11gh10 10i at (¤ 1 = 0°, º = 72.89°, ¤ 2 = 0°) which becomes stronger after warm press deformation.…”
Section: Resultsmentioning
confidence: 49%
“…al. during combination of rolling and high-temperature annealing of AZ31 alloy [25]. The microstructural features shown in figure 2 are due to the fact that a high degree of deformation gives rise to a high fraction of DRX structure.…”
Section: Methodsmentioning
confidence: 99%
“…The microstructural features shown in figure 2 are due to the fact that a high degree of deformation gives rise to a high fraction of DRX structure. Moreover, examination of the microstructural development in AZ31 for different rolling reductions per pass revealed that rolling reductions larger than 53% at warm rolling temperature result in a high fraction of shear banding [25]. It is well known that a shear band is one of the microstructural features that evolve under inhomogeneous deformation [26].…”
Section: Methodsmentioning
confidence: 99%
“…111) In these alloy sheets, texture formation during rolling is suppressed by specialized rolling techniques such as shear rolling, 15) high-temperature rolling, 310) and high-temperature annealing with subsequent warm-rolling. 11) In addition, new alloy design technologies for the improvement of roomtemperature formability have also been developed, in which special elements such as rare-earth metals and calcium, are added in minute quantities to the MgZn alloys. 12,13) It is well known that compared to various other metals, pure Mg has high damping properties.…”
Section: Introductionmentioning
confidence: 99%